A rapid on-line non-chromatographic hydride generation atomic fluorescence spectrometry technique for speciation of inorganic arsenic in drinking water. (30th August 2019) - Alp, Orkun; Tosun, Gokce
Highlights: Rapid inorganic arsenic speciation without chromatographic technique. Determination of iAs (III) and iAs (V) species within a single run. On-line pre-reduction of iAs (V) occurs in less than 1 min. Uniform sensitivity is achieved for iAs (III) and reduced iAs (V). Abstract: A rapid on-line non-chromatographic hydride generation atomic fluorescence spectrometry is described and determination of inorganic arsenic (iAs (III) and iAs (V)) species is achieved within a single run. Thioglycolic acid (TGA) was used for on-line pre-reduction of iAs (V) and quantification of arsenic species was accomplished via calibration with one As form; as iAs (III). Samples and calibration standards were prepared in Tris buffer (pH:7.2) for selective hydride generation and without on-line pre-reduction, iAs (V) signal was negligible up to 150 ng ml −1 . The limit of detection (LOD) values for iAs (III) and iAs (V) were 27 pg ml −1 and 36 pg ml −1, respectively. Recovery studies were performed, certified reference material (TMDA-61) was used to test the accuracy of the method and the results were in good agreement. iAs (V) was the main form in all water samples whereas iAs (III) concentration was <LOD value for some samples.